Biomechanical microsystems : design, processing and applications /: design, processing and applications. (2017) - Ostasevicius, Vytautas; Janusas, Giedrius; Palevicius, Arvydas; Gaidys, Rimvydas; Jurenas, Vytautas
No abstract available